A STUDY OF SELECTED MICROGREENS IN SOIL-LESS MEDIA (International Association of Biologicals and Computational Digest, 2022)
Growing microgreens in soilless media is a very easy task. Here, coco peat and Rice husk are used as growing media. Microgreens are considered as a very good diet source and consumed for good health. They are rich in vitamins and carotenoids. Microgreens are miniature form of leafy vegetables and can be grown anywhere. Carrot, Radish, and Spinach microgreens are taken for the present study in mixture of soilless media. Comparatively a good result was achieved in soilless mixture as media than soil.
Keywords: Micro greens, Coco peat, Rice husk, Carrot, Radish, Spinach, Soilless.